Critique of schooling : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Education - Hawkins, James Ernest (Massey University, 1971)
At one time compulsory schooling was a social gain. On the one hand children were released from economic exploitation and servitude. On the other they were to be released from the bondage of ignorance, and initiated into the lush areas of knowledge which had been previously reserved for a privileged few. Social change does occur, however, and changes in society and people can render formerly useful social arrangements inappropriate. The simple message contained in the discussion below is that 'schooling', as currently conceived and implemented is a pernicious anachronism. The shadow of schooling has, according to a number of commentators, cast an unhealthy darkness over increasing numbers of persons. Schooling, to them, produces the alienated, the intellectually rigid, the inadequate, the non-self-actualising, the fearful, the recipients of 'trained incapacity'. Farber (1969)(1) presents a passionate portrayal of the plight of the pupil within the jaws of schooling. He asserts that schooling does not liberate, rather it encapsulates and represses. To him schooling does not keep abreast of social change, it tenaciously and viciously attempts to press children into moulds which are no longer appropriate. Also, it is not only the outmoded content and objectives which are alone corrosive, but the mode of functioning too.
Keywords: Education; Philosophy